2016
DOI: 10.1038/nm.4219
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide CRISPR screens reveal a Wnt–FZD5 signaling circuit as a druggable vulnerability of RNF43-mutant pancreatic tumors

Abstract: Forward genetic screens with CRISPR-Cas9 genome editing enable high-resolution detection of genetic vulnerabilities in cancer cells. We conducted genome-wide CRISPR-Cas9 screens in RNF43-mutant pancreatic ductal adenocarcinoma (PDAC) cells, which rely on Wnt signaling for proliferation. Through these screens, we discovered a unique requirement for a Wnt signaling circuit: engaging FZD5, one of the ten Frizzled receptors encoded in the human genome. Our results uncover an underappreciated level of context-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
246
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(256 citation statements)
references
References 36 publications
9
246
0
1
Order By: Relevance
“…This result is in contrast to the induction of noncanonical Wnt signaling by Wnt7a via FZD10 (57). In agreement with our results, it has been recently demonstrated that pancreatic cancer cells that mainly secrete Wnt7b are dependent on FZD5 (58). The focus of this study was the canonical Wnt signaling pathway.…”
Section: Discussionsupporting
confidence: 93%
“…This result is in contrast to the induction of noncanonical Wnt signaling by Wnt7a via FZD10 (57). In agreement with our results, it has been recently demonstrated that pancreatic cancer cells that mainly secrete Wnt7b are dependent on FZD5 (58). The focus of this study was the canonical Wnt signaling pathway.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, high FZD receptor expression at the cell surface contributes to overactive Wnt signaling in subsets of pancreatic, ovarian, gastric, and colorectal tumors (16)(17)(18)(19). Recently, antibody-mediated inhibition of FZD5 demonstrated a role for this receptor in pancreatic ductal adenocarcinoma and colorectal carcinoma models (20). Altogether, these findings highlight the importance of FZD receptors in Wnt-dependent stem cell and cancer biology.…”
mentioning
confidence: 88%
“…FZD6 upregulation in colorectal cancer, neuroblastoma and triple-negative breast cancer is involved in stem-like features, EMT and drug resistance (193196). Based on FZD5 upregulation in solid tumors, including RNF43 -mutated pancreatic cancer (197,198), FZD7 upregulation in breast cancer, colorectal cancer, glioma and hepatocellular carcinoma (199203) and FZD10 upregulation in breast cancer, colorectal cancer and synovial sarcoma (204207), anti-FZD5 IgG, anti-FZD7 mAb and anti-FZD10 mAbs have been developed for cancer therapy. Vantictumab (OMP-18R5), initially isolated as an FZD7-binding antibody, is a broad-spectrum anti-FZD mAb that reacts with FZD1, FZD2, FZD5, FZD7 and FZD8 (208), which all belong to the FZD1/2/7 or FZD5/8 subfamily among the FZD family (204).…”
Section: Therapeutics Targeting Wnt Signaling Cascadesmentioning
confidence: 99%